FUTURO DO PRESENTE Narrativas ficcionais acerca do futuro e projeções teóricas relativas a seres artificiais - D’ORNELLAS, PAMELLA REGINA (2019)
This research, whose theme consists of audiovisual fiction narratives related to robots, androids and artificial intelligence, starts from the hypothesis that narratives may have relation with future technological achievements, in addition to creating cultural, social and scientific tendencies. The object of this research are science fiction films that bring the technological approach with the insertion of characters that represent autonomous artificial beings. The study of bibliography and texts related to the theme is followed by a broad mapping of the films studied. Based on the fundamentals of science fiction and discussions of the relationship and interaction between art and technology, some films are selected for content analysis, methodology used to study data collected. Finally, with the presentation of proposals by contemporary futurist authors, some directions are explored that technology, with a focus on robotics and artificial intelligence, tends to follow in the near or distant future. The research reveals an important contribution to the field of Communication in the study and deepening of questions related to the cinematographic narrative and to the technological representations.